Tie-mediated signal from apoptotic cells protects stem cells in Drosophila melanogaster - Xing, Yalan (Nat Commun, 2015)
Many types of normal and cancer stem cells are resistant to killing by genotoxins, but the mechanism for this resistance is poorly understood. Here we show that adult stem cells in Drosophila melanogaster germline and midgut are resistant to ionizing radiation (IR) or chemically induced apoptosis and dissect the mechanism for this protection. We find that upon IR the receptor tyrosine kinase Tie/Tie-2 is activated, leading to the upregulation of microRNA bantam that represses FOXO-mediated transcription of pro-apoptotic Smac/DIA-BLO orthologue, Hid in germline stem cells. Knockdown of the IR-induced putative Tie ligand, Pvf1, a functional homologue of human Angiopoietin, in differentiating daughter cells renders germline stem cells sensitive to IR, suggesting that the dying daughters send a survival signal to protect their stem cells for future repopulation of the tissue. If conserved in cancer stem cells, this mechanism may provide therapeutic options for the eradication of cancer.